Construction forSmart Cleaning Management using IoT Based on Digital Signage (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In particular, changes in digital signage technology are developing in various waysdue to the development of advanced convergence technologies. With the development ofconvergence technologies, digital signage has been constructed to provide informationthrough a structured structure between each component in order to develop in a form that candeliver information in response to environmental changes rather than user input. This paperdeveloped a system that outputs and services various contents together with industrial facilityinspection and management by using wireless communication Bluetooth in a display deviceequipped with an operating system